Krigsspill i operasjonsplanlegging: Hva kan datasimuleringer bidra med? - Karsten Bråthen (Scandinavian Journal of Military Studies, 2022)
Wargames play a key role in operational planning, both for developing alternative courses of actions (COAs) and for developing the plan based on a selected COA. Performing wargames in a command post environment impose strict time and resources constraints compared to other applications of wargaming. Computer-based support, especially computer (constructive) simulations, enables the possibility to wargame many alternative COAs, perform analyses that are more detailed or spend less time on the wargaming activities. This support contributes to better plans produced in a shorter time. The paper describes wargaming in the Norwegian Army’s Plan and Decision Process and based on this derives simulation requirements and outlines how simulations can support the wargaming. Simulations may e.g. perform the role as book-keeper for all the different factors and time-space considerations affecting a COA. Combat simulation may assist in the adjudication process. It is argued how technologies like distributed simulation, command and control and simulation interoperability and terrain analyses meet the needs and requirements. Additionally, the simulation system needs to be easy to use, set up and manage and these requirements can be fulfilled by access from familiar web browsers and a simulation service oriented architecture and infrastructure. SWAP, Simulation-supported Wargaming for Analysis of Plans, is a research proof of concept demonstrator for technologies for wargaming for operational planning. SWAP is also being used to elicit user requirements. A SWAP wargame experiment with 52 cadets from the Norwegian Military Academy, showed that they were able to use the demonstrator after a brief introduction, and explore COAs and produce a decision brief fast, despite SWAP’s limited functionality.   Sammendrag Krigsspill er en sentral aktivitet i operasjonsplanlegging for både å utvikle alternative handlemåter og utvikle plan basert på valgt handlemåte. Å gjennomføre krigsspill i et operativt miljø har stramme føringer i forhold til gjennomføring av krigsspill for andre formål og i andre miljøer. Bruk av simuleringer vil kunne gjøre at det er mulig å krigsspille flere alternative handlemåter, gjøre dypere analyser eller bruke mindre tid. Krigsspill i Hærens plan- og beslutningsprosess blir gjennomgått og hvilke krav som settes til simulering som skal støtte gjennomføring av krigsspillene blir utledet. Hvilken støtte simuleringer kan gi blir gjennomgått sammen med den teknologien som kan gi en slik støtte. SWAP (Simulation–supported Wargaming for Analysis of Plans) er en forskningsdemonstrator som Forsvarets forskningsinstitutt har utviklet over mange år for å evaluere teknologi og innhente brukerkrav. SWAP blir beskrevet og et eksperiment med bruk av SWAP hvor 52 kadetter fra Krigsskolen deltok blir gjennomgått. Til slutt gis det noen betraktninger om bruk av systemer som SWAP i militærutdanning og mulighet som SWAP gir for forskning på den anvendelsen.   Stikkord: Krigsspill; Strids simulering; Plan- og beslutningsprosess; Operasjons planlegging